Analysis of educational report development policies on improving the pedagogy of learning centers - Arief, Hanif; Widodo, Widodo; Rosyanafi , Rofik Jalal (Edukasi, 2024)
This research aims to analyze the Merdeka Belajar development policy, especially through the Education Report Card Platform initiative towards pedagogical practices at PKBM Ar Rayyan, an educational institution that actively adopts innovation to improve the quality of learning. This policy is designed to provide comprehensive data on the achieved effectiveness of teaching methods, with the aim of not only improving the quality of teaching but also to promote the development of tutors' pedagogical competence. This research uses descriptive qualitative research methodology. Through a case study at PKBM Ar Rayyan, it was found that the Education Report Card Platform allows tutors to carry out in-depth self-evaluations, identify and adapt teaching methods to support improving the quality of learning. The platform also encourages productive discussions between tutors and creates a collaborative learning environment. Furthermore, the existence of this platform has become a motivational tool for tutors to develop themselves and adopt innovative teaching strategies. This research shows that the use of the Education Report Card Platform contributes significantly to improving the quality of education through the development of more effective pedagogical practices.